Caffeine consumption during pregnancy and ADHD at the age of 11 years: a birth cohort study - Tiago N Munhoz; Iná S Santos; Alicia Matijasevich; Luciana Anselmi; Bianca Del-Ponte; Luciana Tovo-Rodrigues (BMJ Open, 2016)
Objective Studies evaluating caffeine intake during pregnancy and long-term outcomes, such as the child's neurobehaviour, are still scarce and their results are inconsistent. The objective of the present study was to evaluate the association between maternal consumption of caffeine during pregnancy and attention deficit hyperactivity disorder (ADHD) at the age of 11 years.Methodology All children born in the city of Pelotas, Brazil, during the year 2004, were selected for a cohort study. The mothers were interviewed at birth to obtain information on coffee and yerba mate consumption during pregnancy, among other matters. At the age of 11 years, presence of ADHD was evaluated using the Development and Well-Being Assessment (DAWBA) questionnaire, applied to the mothers. The prevalence of ADHD was calculated, with 95% CIs. The association between caffeine consumption and ADHD was tested by means of logistic regression.Results 3485 children were included in the analyses. The prevalence of ADHD was 4.1% (95% CI 3.4% to 4.7%): 5.8% (95% CI 4.7% to 6.9%) among boys and 2.3% (95% CI 1.5% to 3.0%) among girls. The prevalence of caffeine consumption during the entire pregnancy and in the first, second and third trimesters was 88.7% (87.7% to 89.7%), 86.5% (85.4% to 87.5%), 83.0% (81.8% to 84.2%) and 92.3% (91.4% to 93.1%), respectively. Caffeine consumption during the entire pregnancy and the first, second and third trimesters were not associated with ADHD in the crude or adjusted analysis.Conclusions The present study did not show any association between maternal caffeine consumption during pregnancy and ADHD at the age of 11 years.